PROPORSI JENIS KELAMIN SAPI POTONG YANG DIPOTONG DI RUMAH PEMOTONGAN HEWAN GIWANGAN YOGYAKARTA TAHUN 2012 - , MARLINA ANGGRAENI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Beef cattle developed in various regions in Indonesia to be used meat and by-products. Beef cattle are usually slaughtered in slaughterhouses or abattoirs. The function of slaughterhouses is preventing the transmission of zoonosis diseases, the other function is controlling about productive cowâs cutting. The purpose of this thesis is determined the ratio/proportion of gender and background/origin of beef cattle slaughtered in an abattoir Giwangan Yogyakarta in 2012. The material that used are the cows in Giwangan Slaughterhouse, data entry at Giwangan Slaughterhouse and PKL (Praktek Kerja Lapangan) at Giwangan Slaughterhouse since 8th until 13th April 2013. The methods that used are interviews, literature collect, books and the corresponding data that then analyzed and processed by descriptive. In 2012 at Giwangan Slaughterhouse cutting of cow is more than the bull. Total of cows slaughtered in Giwangan Slaughterhouse in 2012 totaled 4,476 tails of 7.455 tails or 60.04% of the total cutting, while the total of steers slaughtered in Giwangan slaughterhouses, Yogyakarta totaled 2.979 tails of 7455 tails or 39.96% of the total cutting. Cutting for cows slaughter in Giwangan Slaughterhouse is done because the cows are not productive, salvage, have an accident, weight below 100 kg/malnutrition, impaired reproduction, and Body Condition Score (BCS) under 2 or above 4.